The TRAPP Subunit Trs130p Interacts with the GAP Gyp6p to Mediate Ypt6p Dynamics at the Late Golgi - Brunet, Stephanie; Saint-Dic, Djenann; Milev, Miroslav P.; Nilsson, Tommy; Sacher, Michael (Frontiers in Cell and Developmental Biology, 2016)
Small GTPases of the Rab superfamily participate in virtually all vesicle-mediated trafficking events. Cycling between an active GTP-bound form and an inactive GDP-bound form is accomplished in conjunction with guanine nucleotide exchange factors (GEFs) and GTPase activating proteins (GAPs), respectively. Rab cascades have been described in which an effector of an activated Rab is a GEF for a downstream Rab, thus ensuring activation of a pathway in an ordered fashion. Much less is known concerning crosstalk between GEFs and GAPs although regulation between these factors could also contribute to the overall physiology of a cell. Here we demonstrate that a subunit of the TRAPP II multisubunit tethering factor, a Rab GEF, participates in the recruitment of Gyp6p, a GAP for the GTPase Ypt6p, to Golgi membranes. The extreme carboxy-terminal portion of the TRAPP II subunit Trs130p is required for the interaction between TRAPP II and Gyp6p. We further demonstrate that TRAPP II mutants, but not a TRAPP III mutant, display a defect in Gyp6p interaction. A consequence of this defective interaction is the enhanced localization of Ypt6p at late Golgi membranes. Although a ypt31/32 mutant also resulted in an enhanced localization of Gyp6p at the late Golgi, the effect was not as dramatic as that seen for TRAPP II mutants, nor was Ypt31/32 detected in the same TRAPP II purification that detected Gyp6p. We propose that the interaction between TRAPP II and Gyp6p represents a parallel mechanism in addition to that mediated by Ypt31/32 for the recruitment of a GAP to the appropriate membrane, and is a novel example of crosstalk between a Rab GAP and GEF.